THE INFLUENCE OF WORK ENVIRONMENT AND EMPLOYEE INTERESTS ON JOB PROMOTION IN PT AEROFOOD INDONESIA SURABAYA BRANCH OF 2024 - Iswandi , Fahmi Putra; Sholihin , Achmad (Universitas Islam Lamongan, 2024)
Abstract This study aims to examine the influence of work environment and employee interests on job promotion. This study was conducted on the employees of PT Aerofood Indonesia Surabaya Branch using an online survey method. Samples were calculated using Slovin's formula with a confidence level of 10%. Samples analyzed were 70 respondents. The study was conducted using a quantitative method. The analysis technique used was multiple regression analysis using SPSS. The results of the study showed that work environment has a significant influence on job promotion, while employee interest does not have a significant influence on job promotion. Keywords: Work Environment, Employee Interests, Job Promotion